The Role of Artificial Intelligence in Personal Finance (Eurasian Journal of History, Geography and Economics, 2024)
This article provides information on how artificial intelligence can regulate personal income and its role in personal finance. Future retirement planning, current societal challenges related to healthcare systems, and environmental changes require households to pay more attention to their personal finances. This, in turn, calls for a radical change and expansion of the above-mentioned areas. To do this, personal finance will also need to use the increasingly powerful tools of artificial intelligence. The literature review underlying this article: first, transformation shows that credit is a flow of personal finance that is more than necessary, not only in the insurance or payments sector, but also in investment-related situations. Second, through the use of artificial intelligence, simple digitization concepts are pushing the productivity levers that are driving the transformation of the industry more than ever before. Over the next two years, investment products use cases/businesses should focus more on digitalization of their distribution chain.